Prevalence of musculoskeletal pain among undergraduate students - Kandasamy, Geetha; Almanasef, Mona; Almeleebia, Tahani; Orayj, Khalid; Shorog, Eman; Alshahrani, Asma M.; Prabahar, Kousalya; Veeramani, Vinoth Prabhu; Amirthalingam, Palanisamy; Alqifari, Saleh F.; Alrashidi, Fayez; Aldurum, Muteb; et al. (Frontiers in Medicine, 2024)
Musculoskeletal disorders (MSDs) are rapidly rising in Saudi Arabia, reaching levels similar to those of the western world. Hence, we aimed to assess the prevalence of neck, shoulder, and low-back pains (Musculoskeletal Pain-MSP) among students at King Khalid University in Abha, Saudi Arabia.This cross-sectional study was conducted at King Khalid University in Abha, Saudi Arabia, from March 2023 to August 2023. The inclusion criteria were university students aged 18 years and older of both genders who agreed to participate in the study. The modified Nordic questionnaire was used, which comprised three parts.Out of 536 respondents, 337 were female, while 199 were male. The average body mass index (BMI) of the study population was 25.3 ± 4.01. 223 (41.60%) had a history of MSDs. Only 232 (43.28%) of the population did regular exercise. According to multiple logistic regression analysis, factors associated with MSD are mobile device use (with both hands) with a large neck tilt below the horizon line position (OR =2.276, C.I 1.178 to 4.397, p=0.014), family history of trauma (OR =5.450, 95% CI 3.371 to 8.811, p = 0.000), family history of MSD (OR =4.241, 95% CI 2.296 to 7.835, p = 0.000), coffee consumption (OR =1.967, C.I 1.281 to 3.020, p=0.002), and time spent on electronic devices: 1-3 hours (OR =0.252, 95% CI 0.124 to 0.511, p = 0.0001), 4-6 hours (OR =0.455, 95% CI 0.237 to 0.873, p = 0.018), and 6-9 hours (OR =0.348, 95% CI 0.184 to 0.660, p = 0.001).The present study concludes musculoskeletal pain among university students is high. A history of trauma, a family history of MSD, the hand and neck position when using electronic devices, the amount of time spent using them, and regular exercise are risk factors that are strongly associated with MSP. There is strong evidence to suggest that increasing physical activity plays a significant role in enhancing the functionality of the musculoskeletal system and alleviating pain. It is recommended that universities should implement educational programs to raise awareness and health screenings about the impact of device usage on musculoskeletal health and the benefits of regular exercise.